CHARACTER BUILDING ANAK USIA DINI MELALUI OPTIMALISASI FUNGSI PERMAINAN TRADISIONAL BERBASIS BUDAYA LOKAL - Rifa Suci Wulandari; Hestri Hurustyanti (Indonesian Language Education and Literature, 2016)
This research aims to know the application of traditional games based on local culture to develop honesty character and its supporting and obstructing factors at TK Pancasila. The researcher used qualitative descriptive research. The research analysis used was qualitative analysis using the following steps: (1) Collecting the data through observation, interview, and attitude scale test, (2) Reducing the data, (3) Presenting the data, and (4) Concluding and verifying. The research result at TK Pancasila showed that the stages of traditional games application included: (1) Planning stage, (2) Applying traditional games stage in three activities (opening, main activity and closing), and (3) Evaluating stage. The result from pretest and posttest can be concluded that the result of traditional games in developing honesty character for young learners at TK Pancasila was the changing of individual character shown from the increase of honesty character quality as the effect of learning process from experience in playing traditional games. The supporting factors of applying traditional games at TK Pancasila included: (1) Structured curriculum, (2) Fairly high playing motivation from young learners, (3) Conducive facilities and environment to support the process of applying traditional games. The obstructing factors included: (1) The unstable young learners concentration, (2) The minimum time used for traditional games activity, (3) Limited knowledge from teachers about kinds of traditional games used in teaching especially to improve honesty character development from young learners.